2003
DOI: 10.1177/0145482x0309700402
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Diagnostic Intervention Model for Fostering Harmonious Interactions between Deaf-Blind Children and Their Educators

Abstract: This article demonstrates the use of the Diagnostic Intervention Model in everyday practice and the effects of its application in a case study of Kris and his educator using individual coaching. The implications of the case for everyday practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 24 publications
3
66
0
5
Order By: Relevance
“…The changes in affective mutuality were also not The lower rate of confirmation indicates a more ''distant'' interactive style among caregivers with dismissing attachment representations, which might be explained from the general strategy to prevent exposure to negative affect in relationships (Kobak, Cole, Ferenz-Gillies, & Fleming, 1993;Roisman, 2006). However, for clients with visual and intellectual disabilities, confirmation of signals works as a constant reminder that a partner is available for engaging in interaction (Janssen et al, 2003b). In the long run, therefore, the quality of interaction with caregivers with dismissing attachment representations may continue to be relatively more at risk, despite the positive effects of the Contact intervention on the two other dimensions of interaction.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The changes in affective mutuality were also not The lower rate of confirmation indicates a more ''distant'' interactive style among caregivers with dismissing attachment representations, which might be explained from the general strategy to prevent exposure to negative affect in relationships (Kobak, Cole, Ferenz-Gillies, & Fleming, 1993;Roisman, 2006). However, for clients with visual and intellectual disabilities, confirmation of signals works as a constant reminder that a partner is available for engaging in interaction (Janssen et al, 2003b). In the long run, therefore, the quality of interaction with caregivers with dismissing attachment representations may continue to be relatively more at risk, despite the positive effects of the Contact intervention on the two other dimensions of interaction.…”
Section: Discussionmentioning
confidence: 95%
“…Such programs are especially important when persons with disabilities live in group homes, away from their parental attachment figures, have developed highly idiosyncratic, mostly nonverbal means to express their emotional needs, or display aversive behaviors that interfere with positive, harmonious interaction (Janssen, Riksen-Walraven, & Van Dijk, 2003b;Janssen, Schuengel, & Stolk, 2002;Schuengel et al, 2010). Most programs train staff in general skills for interacting with persons with intellectual or multiple disabilities (e.g., Maes, Lambrechts, Hostyn, & Petry, 2007).…”
Section: Representational Processes and Intervention Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…For a variety of reasons, children and youth who are deafblind with additional disabilities have been considered to be particularly vulnerable to toxic stress (Chess, Korn, & Fernandez, 1971;Janssen, Riksen-Walraven, & van Dijk, 2003;McInnis & Treffry, 1982). Communicative behaviors of children who are deafblind are often subtle and difficult to interpret, and as a result, such behaviors are often missed or misinterpreted.…”
mentioning
confidence: 99%
“…Such perceived sudden changes in the environment, in the absence of resources to adjust to them, are likely to evoke stress responses (Janssen, Schuengel, et al, 2002). In addition, research has suggested that children who are deafblind are at increased risk for impaired attachment relationships due to a number of factors including frequent hospitalizations, lack of face-to-face eye contact, lack of joint attention, slow, difficult to read responses to caregiver initiations, and difficulties in regulation of arousal patterns (Janssen et al, 2003;Nelson et al, 2002;Nelson, van Dijk, Oster, & McDonnell, 2009;Rowland, 1984). Moreover, chronic stress in children who are deafblind has been thought to manifest itself in physical illness, self-abusive behaviors, and severe challenging behaviors (Janssen, Schuengel, et al, 2002).…”
mentioning
confidence: 99%